2019
DOI: 10.1021/acssuschemeng.9b03455
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Eutectic Solvents to Overcome Limited Substrate Solubility in the Enzymatic Decarboxylation of Bio-Based Phenolic Acids

Abstract: Phenolic acid decarboxylase from Bacillus subtilis (BsPAD) converts several p-hydroxycinnamic acid derivatives into the corresponding phydroxystyrenes, which are considered to be promising bio-based aromatic chemicals. Despite the enzyme's high activity and stability, the low solubility of its substrates presents severe limitations for the establishment of industrial processes. Accordingly, deep eutectic solvents (DESs) have emerged as interesting alternatives to aqueous or organic solvents and biphasic system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…We recently showed the excellent compatibility of BsPAD with DESs. 36 Choline chloride (ChCl)based eutectic mixtures were tested neat and in dilution with potassium phosphate buffer (50 mM, pH 6.0) for the decarboxylation of a variety of phenolic acid derivatives. Our results proved that not only the free enzyme, but also immobilized PAD shows excellent activity in deep eutectic solvents.…”
Section: Decarboxylation In Batchmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed the excellent compatibility of BsPAD with DESs. 36 Choline chloride (ChCl)based eutectic mixtures were tested neat and in dilution with potassium phosphate buffer (50 mM, pH 6.0) for the decarboxylation of a variety of phenolic acid derivatives. Our results proved that not only the free enzyme, but also immobilized PAD shows excellent activity in deep eutectic solvents.…”
Section: Decarboxylation In Batchmentioning
confidence: 99%
“…Recent findings showed that PAD is highly active in DES. 36 Experiments on interactions of the used DES and the biocatalyst were not coducted so far and are not scope of this work. A series of recently investigated DES-protein systems can be found in literature.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 30 % the cosolvent ethanol for the Heck reaction further diluted the reaction solution. PAD from Bacillus subtilis shows very good activity in a mixture of choline chloride:glycerol (1 : 1) with 50 % (v/v) water, which allowed to increase the substrate solubility dramatically . Due to the high viscosity of pure DES‐solutions, a 50 % mixture with water appeared to be highly suitable for a continuous approach.…”
Section: Chemoenzymatic Synthetic Cascadesmentioning
confidence: 99%
“…PAD from Bacillus subtilis shows very good activity in a mixture of choline chloride: glycerol (1 : 1) with 50 % (v/v) water, which allowed to increase the substrate solubility dramatically. [28] Due to the high viscosity of pure DES-solutions, a 50 % mixture with water appeared to be highly suitable for a continuous approach. In a first, enzymatic step, a 70 mM solution of coumaric acid was decarboxylated by PAD encapsulated in alginate beads at 30°C.…”
Section: Javiermentioning
confidence: 99%
“…The resulting styrene derivatives are of great industrial relevance since the terminal alkene provides a versatile handle for further chemical functionalization or polymerization reactions [16][17][18]. In contrast to other (de)carboxylases, several PADs found in bacteria [19][20][21][22] and plants [23] act on an acid-base mechanism via a quinone methide intermediate [24] and do not require a cofactor, therefore eliminating the need of a laborious and expensive cofactor regeneration system [25,26].…”
Section: Introductionmentioning
confidence: 99%